Estimation of efficiency of new local rehabilitation method at the early post-operative period after dental implantation - Pasechnik, A. V.; Kravchenko, L. S.; Pasechnik, A. M.; Lungu, V. I.; Lozenko, P. A. (Journal of Education, Health and Sport, 2017)
Pasechnik А. V., Kravchenko L. S., Pasechnik A. M., Lungu V. I., Lozenko P. A. Estimation of efficiency of new local rehabilitation method at the early post-operative period after dental implantation. Journal of Education, Health and Sport. 2017;7(1):408-422. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.290607 http://ojs.ukw.edu.pl/index.php/johs/article/view/4260 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. UDK 616.314–089.843–06–084 ESTIMATION OF EFFICIENCY OF NEW LOCAL REHABILITATION METHOD AT THE EARLY POST-OPERATIVE PERIOD AFTER DENTAL IMPLANTATION А. V. Pasechnik, L. S. Kravchenko, A. M. Pasechnik, V. I. Lungu, P. A. Lozenko Odessa National Medical University, Odessa Summary Despite of success of dental implantation, there are often complications at the early post-operative period of implant placing associated with wound damage and aseptic inflammation. Purpose of the work is studying clinical efficiency of combined local application of new mucosal gel “Apior” and magnetotherapy at the early post-operative period after dental implantation. Combined local application of the mucosal gel “Apior” and pulsating low-frequency electromagnetic field in the complex medical treatment of patients after conducting an operation of setting dental implants favourably affects the common state of patients and clinical symptoms of inflammation in the area of operating wound. As compared with patients who had traditional anti-inflammatory therapy, the patients treated with local application of apigel and magnetoterapy had decline of edema incidence, of gingival mucosa hyperemia, of discomfort in the area of conducted operation. There occurred more rapid improvement of inflammation painfulness, which correlated with the improvement of hygienic state of oral cavity and promoted to prevention of bacterial content of damaged mucous surfaces. Estimation of microvasculatory blood stream by the method of ultrasonic doppler flowmetry revealed more rapid normalization of volume and linear high systole speed of blood stream in the periimplant tissues in case of use of new complex local rehabilitation method, that testified to the less pronounced inflammation of oral mucosa after the operation. The authors came to conclusion that the local application of the offered method of medical treatment of early post-operative complications of dental implantation reduces terms of renewal of structural-functional integrity of oral mucosa, helps in preventing development of inflammatory complications and strengthening endosseus implant. The inclusion in the treatment management of a new combined method of application of mucosal gel “Apior” and magnetotherapy at the early post-operative period of dental implantation improves the hygienic state of oral cavity, positively affects nonspecific resistance of oral liquid, renders the regenerative action on oral mucosa tissues, which improves efficiency of medical treatment and quality of life of patients. Key words: dental implantation, magnetotherapy, mucosal apigel, inflammation, microvasculation.